Doping-dependent superconducting properties of two-dimensional metals with different types of interparticle coupling (Review Article): - Loktev, Vadim M.; Turkowski*, Vladimir M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The superconducting properties of a two-dimensional metallic system with arbitrary carrier density and both local and various types of the indirect boson-exchange attractive interaction in the cases of s- and d-wave pairing are analyzed and reviewed at T = 0. In particular, the possibility of a crossover from the Bose—Einstein condensation regime to Bardeen—Cooper—Schrieffer-like superconductivity with growing carrier density and changing coupling in the case of different pairing channels is discussed. Gaussian fluctuations of the order parameter are taken into account, andthe carrier density dependence of the gap magnitude is studied. The role of the form of the interparticle attractive interaction in the physical behavior of the system is also considered.